Bank Concentration and Economic Volatility in the OIC Countries: The Role of Financial Development - Edib Smolo (Croatian Economic Survey, 2022)
This study examines the effect of bank concentration and financial development on economic volatility in member countries of the Organization of Islamic Cooperation (OIC). Using the GMM estimator, we cover the 2000–2017 period. Based on both linear and non-linear estimations, we find no significant impact of bank concentration on economic volatility. By contrast, financial development reduces economic volatility. Moreover, the relationship between concentration and volatility is influenced by financial development. Considering this, policymakers should put more emphasis on developing the financial sector than controlling bank concentrations. We find that our findings remain robust in the face of different specifications and proxies used to measure bank concentration and financial development.